Prediction of surface roughness of ti-6al-4v in electrical discharge machining: a regression model - Khan, Md. Ashikur Rahman; Rahman, M. M.; Kadirgama, Kumaran; Maleque, Md. Abdul; Ishak, M. (University Malaysia Pahang, 2011)
This paper develops a single order mathematical model for correlating various electrical discharge machining (EDM) parameters and performance characteristics by utilizing relevant experimental data obtained through experimentation. In addition to the effect of peak ampere, the effect of pulse on time and pulse off time on surface roughness has also been investigated. Experiments have been conducted on titanium alloy Ti-6Al-4V with a copper electrode retaining negative polarity as per the Design of Experiments. Response surface methodology techniques are utilized to develop the mathematical model as well as to optimize the EDM parameters. An analysis of variance has been performed for the validity test of fit and adequacy of the proposed models. It can be seen that increasing pulse on time causes a fine surface until a certain value, beyond which the surface finish deteriorates. The excellent surface finish is investigated in this study for the case of pulse on time below 80 μs. This result acts as a guide for selecting the required process outputs and most economic industrial machining conditions for optimizing the input factors.